A Systematic Review of the Virtues and Vices of Exit Exams in Higher Education - Teshome, Samson Worku (Darul Yasin Al Sys, 2025)
Exit exams in higher education have become central tools for assessing students' readiness for professional roles or advanced academic pursuits, aiming to uphold accountability, standardization, and quality assurance across educational systems. Designed to evaluate mastery of discipline-specific knowledge, skills, and competencies, their implementation has sparked ongoing debate about their effectiveness and equity. This systematic literature review synthesizes findings from 33 peer-reviewed studies to examine both the advantages and challenges associated with exit exams. The review identifies that exit exams enhance transparency, promote comparability, and align academic outcomes with labor market expectations. However, they also present significant drawbacks, including the risk of over-standardization, elevated psychological stress, and reinforcement of systemic biases. Marginalized student populations are often disproportionately affected, as high-stakes testing can deepen existing educational inequalities and promote surface-level learning due to a